2012
DOI: 10.1016/j.neuron.2011.12.040
|View full text |Cite
|
Sign up to set email alerts
|

A Network Diffusion Model of Disease Progression in Dementia

Abstract: SUMMARY Patterns of dementia are known to fall into dissociated but dispersed brain networks, suggesting that the disease is transmitted along neuronal pathways rather than by proximity. This view is supported by neuropathological evidence for “prion-like” transsynaptic transmission of disease agents like misfolded tau and beta amyloid. We mathematically model this transmission by a diffusive mechanism mediated by the brain’s connectivity network obtained from tractography of 14 healthy-brain MRIs. Subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

46
713
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 625 publications
(762 citation statements)
references
References 58 publications
46
713
1
2
Order By: Relevance
“…Deviations from normal trajectories of brain maturation have been identified in developmental disorders (38,48), while some neurodegenerative disorders seem to progress within specific healthy brain networks (23,49). One recent study has also shown that data-driven decomposition of white matter tractograms in healthy young subjects recapitulates the pattern of abnormalities in dementia (50). Here, we show how the symmetric inverted-U component, while derived without any prior hypothesis from healthy subjects' brain structure, (i) spatially recapitulates the structural vulnerability of two etiologically distinct disorders emerging at opposite ends of the life spectrum (schizophrenia-aptly named "dementia praecox" until the mid1950s-and Alzheimer's disease), (ii) accurately discriminates these two disorders from their matched healthy group, and (iii) is associated, in this large-scale lifespan healthy population, with cognitive functions whose impairment are key symptoms of schizophrenia and Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Deviations from normal trajectories of brain maturation have been identified in developmental disorders (38,48), while some neurodegenerative disorders seem to progress within specific healthy brain networks (23,49). One recent study has also shown that data-driven decomposition of white matter tractograms in healthy young subjects recapitulates the pattern of abnormalities in dementia (50). Here, we show how the symmetric inverted-U component, while derived without any prior hypothesis from healthy subjects' brain structure, (i) spatially recapitulates the structural vulnerability of two etiologically distinct disorders emerging at opposite ends of the life spectrum (schizophrenia-aptly named "dementia praecox" until the mid1950s-and Alzheimer's disease), (ii) accurately discriminates these two disorders from their matched healthy group, and (iii) is associated, in this large-scale lifespan healthy population, with cognitive functions whose impairment are key symptoms of schizophrenia and Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
“…These disorders feature the accumulation of fibrillar deposits of the microtubule-associated protein tau with progressive deterioration of the central nervous system. Tau pathology and its associated brain atrophy do not appear randomly throughout the brain, but rather progress along distinct neural networks (1)(2)(3)(4)(5). This aspect suggests a role for transcellular spread of a pathogenic agent via neural connections.…”
mentioning
confidence: 99%
“…Lesions in each of these diseases are initially limited to defined regions of selectively vulnerable neurons, but staging of pathology in Alzheimer's disease (1), Parkinson's disease (2,3), amyotropic lateral sclerosis (4,5), and Huntington's disease (HD) (6) reveal broader deposition of pathological aggregates at more advanced stages of disease progression. The observation that the pathology appeared to progress into regions that were synaptically connected led to the idea that pathology was spreading through neuronal circuits (7,8). Converging lines of evidence demonstrated that aggregates of diseaseassociated misfolded proteins, including α-synuclein, tau, and superoxide dismutase 1, are in fact transmissible from cell to cell and that this transmission propagates throughout the brain (9,10).…”
mentioning
confidence: 99%